2020
DOI: 10.1038/s42003-020-01301-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical landscape of breast cancers with germline BRCA1/2 variants

Abstract: The genetic and clinical characteristics of breast tumors with germline variants, including their association with biallelic inactivation through loss-of-heterozygosity (LOH) and second somatic mutations, remain elusive. We analyzed germline variants of 11 breast cancer susceptibility genes for 1,995 Japanese breast cancer patients, and identified 101 (5.1%) pathogenic variants, including 62 BRCA2 and 15 BRCA1 mutations. Genetic analysis of 64 BRCA1/2-mutated tumors including TCGA dataset tumors, revealed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Consistent with prior studies of ovarian cancers, our results suggest that BRCA1/2 mutation-associated malignancies accrue most of their genomic scarring and mutations early in tumorigenesis, and increasing genomic instability is not a major factor driving recurrence. TP53 was the only established cancer gene consistently mutated in primary and recurrent tumors, necessary to allow cell cycle progress in genomically unstable tumors 29,47,[70][71][72][73] . We found that ER+ BRCA2 mutation-associated breast tumors, as well as tumors with discordant LOH (primary vs. recurrence), were less likely to have TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies of ovarian cancers, our results suggest that BRCA1/2 mutation-associated malignancies accrue most of their genomic scarring and mutations early in tumorigenesis, and increasing genomic instability is not a major factor driving recurrence. TP53 was the only established cancer gene consistently mutated in primary and recurrent tumors, necessary to allow cell cycle progress in genomically unstable tumors 29,47,[70][71][72][73] . We found that ER+ BRCA2 mutation-associated breast tumors, as well as tumors with discordant LOH (primary vs. recurrence), were less likely to have TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 63 BRCA1 genetically deficient cases, matched RNA-seq data were only available from 13 samples in TCGA database. Meanwhile, 16 TCGA breast cancers with germline pathogenic BRCA1 mutation 29 were also identified. On these 29 BRCA1 deficient breast cancers with RNA-seq, we performed the hierarchy clustering analysis based on overall transcriptome and molecular subtyping analysis based on PAM50 according to previous study 30 .…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed a cohort of 1995 unselected Japanese women with primary breast cancer registered at Kyoto Breast Cancer Research Network institutions, including Kyoto University Hospital and 15 affiliated hospitals from September 2011 to October 2016. Genomic DNA samples from the peripheral blood of these patients were analyzed previously 21 . The dataset used in this study was updated with relevant clinical information until December 31, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA samples from the peripheral blood of these patients were analyzed previously. 21 The dataset used in this study was updated with relevant clinical information until December 31, 2019. Written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%